Exploration of stimulating children's naturalistic intelligence at Bahtera Multiple Intelligence Preschool Malaysia - Sugiyana, Lista; Agustin, Mubiar; Muqodas, Idat; Lily Muliana Mustafa (Universitas Nahdlatul Ulama Surabaya, 2025)
Naturalist intelligence is a crucial aspect of early childhood development as it encourages children to recognize and directly interact with the natural environment. However, children's interaction with nature has declined due to the dominance of academic curricula and the increasing use of technology in learning, which limits environmental exploration and potentially hinders their cognitive and social development. Amid these challenges, it is essential to understand how learning strategies can be optimized to stimulate children's naturalist intelligence in a contextual manner that reflects the dynamics of field implementation, the challenges encountered, and the solutions adopted. This study employed a descriptive qualitative method using a case study approach. The research subjects were 12 students at Bahtera Multiple Intelligence Preschool, Malaysia. Data collection techniques included observation, interviews, and documentation of learning activities involving children aged 3–4 years. The results indicate that nature exploration, messy play, and nature walks are effective approaches in stimulating naturalist intelligence. These strategies are supported by the use of indoor exploration spaces and nature-based materials as solutions to external constraints such as weather conditions and high exposure to digital technology among children. These findings contribute to the development of adaptive learning strategies tailored to the characteristics of naturalist intelligence in early childhood.